Prospective validation of a screening tool to identify older adults in need of a driving evaluation - Betz, Marian E. (J Am Geriatr Soc, 2017)
BACKGROUND/OBJECTIVES: In at-risk older drivers, behind-the-wheel (BTW) tests can assess skills and inform vehicle modifications, retraining or, if necessary, the need for driving retirement. We sought to prospectively validate and refine the five-item “CRASH” screening tool for identifying older drivers needing a BTW test. DESIGN: Prospective observational study. SETTING: Geriatric and internal medicine primary care clinics affiliated with a tertiary care hospital, and a local BTW program. PARTICIPANTS: 315 cognitively-intact drivers aged ≥65 years. MEASUREMENTS: Participants completed: baseline questionnaire (including CRASH tool) and assessments; BTW test (evaluator blinded to questionnaire results); and one-month telephone follow-up. Analysis included descriptive statistics and examination of predictive ability of the CRASH tool to discriminate “normal” (pass) versus “abnormal” (conditional pass or fail) on the BTW test, with logistic regression and CART techniques for tool refinement. RESULTS: 266 participants (84%) had a BTW test; of these, 17% had a normal and 83% an abnormal rating. Half (45%) of those with an abnormal score were advised to limit driving under particular conditions. Neither the CRASH tool nor its individual component variables were significantly associated with the summary BTW score; in refined models with other variables, the best-performing tool had approximately 67% sensitivity and specificity for an abnormal BTW score. Most participants found the BTW test useful and were willing to pay a median of $50. At one-month follow-up, no participants had stopped driving. CONCLUSION: The CRASH screening tool cannot be recommended for use in clinical practice. Findings on older adults’ perceived utility of the BTW test and the stability of driving patterns at one-month follow-up could be useful for future research studies and for design of older driver programs.